Opportunities and Challenges Mapping for Achieving Energy Transition in Indonesia’s Electricity Sector - Rizky, Muhammad; Suhendra, Maman (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
The climate change phenomena urge the government to develop policies that can anticipate catastrophic losses from climate change, one of which is to reduce emissions in the energy industry, which requires huge of money. This study examines Indonesia's energy transition program, particularly in the power sector, as well as financing methods that primarily use blended finance. This study will then examine the prospects and constraints for financing energy transition program in Indonesia. This study employs a qualitative single case study method, using primary data sources from interviews with policymakers, policy implementers, and academics on the topic of energy transition financing. This study produces mappings of finance opportunities and challenges when Indonesia adopts an energy transition program. This study is expected to contribute to policy considerations for both the government and business sectors involved in implementing Indonesia's energy transition program.